Chronic intermittent toluene inhalation in adolescent rats results in metabolic dysfunction with altered glucose homeostasis. (22nd October 2015) - Dick, A L W; Simpson, A; Qama, A; Andrews, Z; Lawrence, A J; Duncan, J R
Abstract : Background and Purpose: Abuse of toluene‐containing inhalants is an increasing public health problem, especially among adolescents. Abuse during adolescence is associated with emaciation, while industrial exposure leads to altered glycaemic control suggesting metabolic instability. However, the relationship between adolescent inhalant abuse and metabolic dysfunction remains unknown. Experimental Approach: To model human abuse patterns, we exposed male adolescent Wistar rats [postnatal day (PND) 27] to chronic intermittent inhaled toluene (CIT, 10 000 ppm) or air (control) for 1 h·day −1, three times a week for 4 weeks. Feeding and body composition were monitored. After 4 weeks, circulating metabolic hormone concentrations and responses to a glucose tolerance test (GTT) were measured. Dietary preference was measured by giving animals access to either a 'western diet' plus standard chow (WC + SC) or standard chow alone during 4 weeks of abstinence. Metabolic hormones and GTT were subsequently measured. Key Results: Adolescent CIT exposure significantly retarded weight gain, altered body composition, circulating metabolic hormones and responses to a GTT. While reduced body weight persisted, responses to a GTT and circulating hormones appeared to normalize for animals on standard chow following abstinence. In CIT‐exposed WC + SC rats, we observed impaired glucose tolerance associated with altered metabolic hormones. Analysis of hypothalamic genes revealed differential expression profiles in CIT‐exposed rats following both the exposure period and abstinence, suggesting a central contribution to inhalant‐induced metabolic dysfunction. Conclusion and Implications: CIT exposure during adolescence has long‐term effects on metabolic function, which may increase the risk of disorders related to energy balance and glycaemic control.